Needs Analysis Regarding Residents of Environmentally Affected Areas. Patos - Marinza Case - Jance, Marilda (Mediterranean Journal of Social Sciences, 2013)
Societies are faced with the problems which are of many and various, but now days there are increasing evidences on theclose links that exist between environmental problems and social injustice. Various studies tent to place their focus on solvingenvironmental problems through integrated and multi-dimensional social policies. Often the treatment of isolated environmentalpolicies may slow down the progress towards achieving social wellbeing or vice versa. Social and environmental issues canproportionally often be in conflict to each other, but with an integrated package of policies it would be a proper way for avoidingor resolving these conflicts. This study tents to see social injustice issues through environmental lens and vice versa byanalyzing environmental issues more clearly in terms of social justice. New effective ways for dealing with each should bedeveloped rather than each issue is tackled separately. This study is focused on the Marinze (Patos-Fier) area as such as thatin recent years is facing many environmental and social issues and tends to emphasize the needs of the residents referred tothese problems. The data collected through the survey (including open and closed questions), clearly demonstrate the effectson health and livelihoods of the inhabitants facing air pollution, mainly to residents living near sources of pollution. This paperemphasizes the importance that the inclusion of environmental policies in other social policies in order to ensure and enhancethe welfare of individuals and the importance that local institutions should play to ensure and protect the health of residentswho need supportive services.